2015
DOI: 10.3329/bjb.v43i2.21675
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic potential of rhizosphere fungi against leaf spot and fruit rot pathogens of brinjal

Abstract: Antagonistic potentials of seven rhizoshere soil fungi viz., Aspergillus flavus Link., A. fumigatus Fresen., A. niger Tiegh., A. terreus Thom., Penicillium sp., Trichoderma harzianum Refat. and T. viride Pers. were tested in opposition to six pathogenic fungi viz., Colletotrichum sp., Curvularia lunata, Fusarium moniliforme, F. oxysporum, F. semitectum and Phomopsis sp. isolated from different leaf spots and fruit rots of brinjal. Out of seven soil fungi, Trichoderma harzianum was found most effective to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
2
7
10
Order By: Relevance
“…The maximum inhibition of radial growth of C. gloeosporioides was observed in T. viride (77.64%) which was followed by A. flavus (75.58%), A. fumigatus (60.88%) and A. niger (58.23%) due to the volatile metabolites after 6 days of incubation at 25 ± 2ºC. In contrast to the result of present study, Aktar et al (12) reported that volatile metabolites produced by isolates of A. niger, A. flavus, A. fumigatus and T. viride inhibited the mycelial growth of Colletotrichum sp. by 14.68, 11.78, 11 and 11%, respectively.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…The maximum inhibition of radial growth of C. gloeosporioides was observed in T. viride (77.64%) which was followed by A. flavus (75.58%), A. fumigatus (60.88%) and A. niger (58.23%) due to the volatile metabolites after 6 days of incubation at 25 ± 2ºC. In contrast to the result of present study, Aktar et al (12) reported that volatile metabolites produced by isolates of A. niger, A. flavus, A. fumigatus and T. viride inhibited the mycelial growth of Colletotrichum sp. by 14.68, 11.78, 11 and 11%, respectively.…”
Section: Resultscontrasting
confidence: 95%
“…However, grade 2 was found to be the most commonly encountered type of colony interaction as 10 interactions were incorporated in this grade which was followed by grade 4 (2 out of 12 ) (Table 1). In contrast to the present study, Akter et al (12) reported that in dual culture colony interaction A. niger, T. viride, A. flavus and A. fumigatus showed 68.66, 57.24, 54.19 and 50.25% growth inhibition on Colletotrichum sp., respectively. Again Aspergillus niger, Trichoderma viride, A. flavus and A. fumigaus showed 75.87, 75.5, 51.78 and 45.52% growth inhibition on Curvularia lunata, respectively.…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…4 show that out of seven soil fungi Trichoderma harzianum was found most effective to control the growth of both the test pathogens. Akter et al (23) also found the same results against six pathogenic fungi viz., Colletotrichum sp., Curvularia lunata, Fusarium moniliforme, F. oxysporum, F. semitectum and Phomopsis sp. isolated from different leaf spots and fruit rots of brinjal.…”
Section: Dennis and Webstermentioning
confidence: 57%
“…Despite the prevalence and diversity of plantendophytic fungus associations, studies have sought to document the impact of using these fungi on plants of agronomic or medical interest; however, such research is still in its incipient stages when compared with the number of studies on growth promotion conducted with bacteria, especially rhizobacteria, such as Rhizobium, Pseudomonas, Bacillus, Azotobacter and Azospirillum (Ahemad and Kibret, 2014;Bashan et al, 2014;Dutta and Khurana, 2015;Egamberdieva and Lugtenberg, 2014;. Studies using endophytic fungi as growth promoters have thus far been restricted to investigation of their antagonist activity against pathogens (Aktar et al, 2014;Parmar et al, 2015a) and have been much more restrictive than studies conducted with mycorrhizae and non-root rhizosphere fungi. However, new endophytic fungi are frequently isolated and identified as possible inoculants, such as Penicillium funiculosum, Sordariomycetes sp.…”
Section: Discussionmentioning
confidence: 99%